Manipulation of Plant Host Susceptibility: An Emerging Role for Viral Movement Proteins? - Amari, Khalid; Vazquez, Franck; Heinlein, Manfred (Frontiers in Plant Science, 2012)
Viruses encode Viral Suppressors of RNA silencing (VSRs) to counteract RNA silencing, a major antiviral defense response in plants. Recent studies indicate a role of virus-derived siRNAs in manipulating the expression of specific host genes and that certain plant viral movement proteins (MPs) can act as Viral Enhancers of RNA silencing (VERs) by stimulating the spread of silencing between cells. This suggests that viruses have evolved complex responses capable to efficiently hijack the host RNA silencing machinery to their own advantage. We draw here a dynamic model of the interaction of plant viruses with the silencing machinery during invasion of the host. The model proposes that cells at the spreading front of infection, where infection starts from zero and the VSR levels are supposedly low, represent potential sites for viral manipulation of host gene expression by using virus- and host-derived small RNAs. Viral MPs may facilitate the spread of silencing to produce a wave of small RNA-mediated gene expression changes ahead of the infection to increase host susceptibility. When experimentally ascertained, this hypothetical model will call for re-defining viral movement and the function of viral movement proteins.